A constraint programming-based genetic algorithm for capacity output optimization - Kate Ean Nee Goh; Jeng Feng Chin; Wei Ping Loh; Melissa Chea-Ling Tan (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: The manuscript presents an investigation into a constraint programming-based genetic algorithm for capacity output optimization in a back-end semiconductor manufacturing company. Design/methodology/approach: In the first stage, constraint programming defining the relationships between variables was formulated into the objective function. A genetic algorithm model was created in the second stage to optimize capacity output. Three demand scenarios were applied to test the robustness of the proposed algorithm. Findings: CPGA improved both the machine utilization and capacity output once the minimum requirements of a demand scenario were fulfilled. Capacity outputs of the three scenarios were improved by 157%, 7%, and 69%, respectively. Research limitations/implications: The work relates to aggregate planning of machine capacity in a single case study. The constraints and constructed scenarios were therefore industry-specific. Practical implications: Capacity planning in a semiconductor manufacturing facility need to consider multiple mutually influenced constraints in resource availability, process flow and product demand. The findings prove that CPGA is a practical and an efficient alternative to optimize the capacity output and to allow the company to review its capacity with quick feedback. Originality/value: The work integrates two contemporary computational methods for a real industry application conventionally reliant on human judgement.
Keywords: 650; constraint programming; genetic algorithm; semiconductor capacity management; production planning